2016
DOI: 10.1515/znb-2016-0034
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of Cs2S2O3·H2O

Abstract: 2− are coordinated by the alkali metal cations, and in addition they serve as acceptors for hydrogen bonding. For both Cs atoms the shortest distances are observed to oxygen atoms of the S 2 O 3 2− anions whereas the terminating sulfur atom has its shortest contacts to the water hydrogen atoms. Thus, an extended hydrogen bonding network is formed. The title compound has also been characterized by IR spectroscopy. IR spectroscopy reveals the vibrational bands of the water molecules at 3385 cm −1 . They show a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…with the sheer number of references obviously illustrating the high stability of the latter phase. For other alkali metal thiosulfates, the structures of anhydrous K 2 S 2 O 3(Lehner et al, 2013) and K 2 S 2 O 3 Á1/3H 2 O(Csorda ´s, 1969;Chan et al, 2008;Lehner et al, 2013) as well as of the monohydrates of Rb 2 S 2 O 3(Lehner et al, 2013) and Cs 2 S 2 O 3(Winkler et al, 2016) have been reported.…”
mentioning
confidence: 99%
“…with the sheer number of references obviously illustrating the high stability of the latter phase. For other alkali metal thiosulfates, the structures of anhydrous K 2 S 2 O 3(Lehner et al, 2013) and K 2 S 2 O 3 Á1/3H 2 O(Csorda ´s, 1969;Chan et al, 2008;Lehner et al, 2013) as well as of the monohydrates of Rb 2 S 2 O 3(Lehner et al, 2013) and Cs 2 S 2 O 3(Winkler et al, 2016) have been reported.…”
mentioning
confidence: 99%